Noise Exposure of School Teachers – Exposure Levels and Health Effects - Marija HADZI-NIKOLOVA; Dejan MIRAKOVSKI; Milka ZDRAVKOVSKA; Bistra ANGELOVSKA; Nikolinka DONEVA (Archives of Acoustics)
Faculty of Natural and Technical Sciences and Faculty of Medical Sciences starting from December 2012, launched joint study in order to investigate personal noise exposure and associated health effects in general school teachers population, starting from kindergartens up to high schools in Stip, Macedonia. In order to determine workplace associated noise exposure and associated health effects in this specific profession, a full shift noise exposure of 40 teachers from 1 kindergarten, 2 primary and 2 high schools were measured in real conditions using noise dosimeters. A-weighted equivalent-continuous sound pressure levels (LAeq) of each teacher were recorded during single activities (classes). Normalized 8-hours exposure, termed the noise exposure level (Lex;8 h) was also computed. Daily noise dose is another descriptor for noise exposure that was determined as a measure of the total sound energy to which workers have been exposed, as a result of working in the varying noise levels. Health effects were assessed trough a full scale epidemiological study which included 231 teachers from the same schools. Specific questionnaire was used to extract information about subject’s perception on occupational noise exposure, as well as theirs occupational and medical history.